The influence of coping appraisals on the adoption of decentralised water systems in Australia. Issue 1 (2nd January 2017) - Tapsuwan, Sorada; Mankad, Aditi; Greenhill, Murni; Tucker, David
Abstract: In Australia, water scarcity has resulted in the need for re-evaluating demand management policies, as well as the identification of alternative water supplies. Specifically, water utilities have been focusing on increasing the adoption of household level decentralised water systems (DWS). While such engineering solutions may be effective, understanding the factors which influence adoption is crucial for widespread uptake. Protection Motivation (PM) theory was used to assess DWS adoption in a sample of 295 homeowners across South East Queensland, Australia. Results provided good support for the application of PM theory to understanding whether people cope adaptively to water shortage threats. The model's hypothesised link between adaptive coping and behavioural intention was also supported, suggesting PM theory can be used to understand people's intention to adopt DWS in the context of the drought. The predictive ability of the PM model improved significantly when demographic variables – age and perceived water – use were included.